Aspiration Pneumonia: Patophysiology, Diagnosis and Treatment - Kirana, Devi Chandra; Fathana, Prima Belia; Ristia, Ovia Intan; Mario, Andina Nabilah; Lukman, Dian Azizah; Abdiman, I Made Tobias; Putra, Made Raditya Arhya; Salsabila, Maida Sania (Jurnal Biologi Tropis, 2024)
Aspiration pneumonia is one of the diseases that is often hidden and under-recognized. This disease contributes to a higher mortality rate compared to other types of pneumonia. This study aims to analyze the pathophysiology, diagnosis and management of aspiration pneumonia. The method used is a literature study by searching for literature published in PubMed, ScienceDirect, and Researchgate with the keywords "aspiration pneumonia", "aspiration pneumonia pathophysiology", "aspiration pneumonia diagnosis and treatment". Aspiration pneumonia can occur due to micro mechanisms or macro mechanisms. Micro mechanisms are mechanisms that cannot be observed while macro mechanisms often occur due to impaired swallowing. Aspiration experienced by pneumonia patients causes inflammation and disruption of the epithelium. The diagnosis of aspiration pneumonia can be established based on clinical symptoms and supporting examinations such as radiology and laboratory examinations. Management that can be carried out on aspiration pneumonia can be done with pharmacological and non-pharmacological management.